2008
DOI: 10.1007/s11270-008-9820-y
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Fate of the Herbicide MCPA in Two Soils as Affected by the Presence of Wheat Ash

Abstract: This study was conducted to evaluate the environmental fate processes of the herbicide (4-chloro-2-methylphenoxy)acetic acid (MCPA) in agricultural soils in the presence and absence of ash originating from the burning of wheat residue. The ash-amended soils (1% ash by weight) were approximately 8-16 times more effective than the ash-free soils in sorbing MCPA. The desorption results showed that 40-78% of initially sorbed MCPA were desorbed in both soils, depending on the initial MCPA concentration in solution.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 36 publications
2
3
0
Order By: Relevance
“…Bioavailability of diuron to soil microorganisms was decreased by the presence of wheat char in the soil, due to the increase in herbicide sorption. For the weak acidic herbicide MCPA, a decrease in biodegradation because of wheat ash amendment was also reported by Hiller et al (2009). The half-life of MCPA increased by a factor of 4.5 in the sandy loam soil with the 1% (w/w) wheat ash amendment, and correspondingly increased by 2.6 times in the sandy soil.…”
Section: Effect Of Carbonaceous Materials On Pesticide Degradationsupporting
confidence: 57%
“…Bioavailability of diuron to soil microorganisms was decreased by the presence of wheat char in the soil, due to the increase in herbicide sorption. For the weak acidic herbicide MCPA, a decrease in biodegradation because of wheat ash amendment was also reported by Hiller et al (2009). The half-life of MCPA increased by a factor of 4.5 in the sandy loam soil with the 1% (w/w) wheat ash amendment, and correspondingly increased by 2.6 times in the sandy soil.…”
Section: Effect Of Carbonaceous Materials On Pesticide Degradationsupporting
confidence: 57%
“…If the incubation took place at 10°C, MCPA was no longer detectable after 25 days. Similar detection times for MCPA were reported by Baelum et al (2006), Baelum et al (2006), Hiller et al (2009), and Peña et al (2015).…”
Section: Resultssupporting
confidence: 87%
“…Activation of BC3 at 200 °C for 2 h (BC4) slightly increased the sorption of the herbicide on the amended soil, as compared to the sorption on the soil amended with BC3. The effect of wheat ash on MCPA sorption was studied by Hiller et al, 36 who observed a 10À 15-fold increase in K d values when a sandy soil and a sandy loam soil were amended with 1% ash. These authors suggested that the increase of MCPA sorption on the wheat ash amended soils was due to the organic carbon content of the ash and to the greater surface affinity for MCPA.…”
Section: ' Materials and Methodsmentioning
confidence: 99%